(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
Modern professional tennis is characterized by a multi-level system of competitions, in the structure of which the Grand Slam tournaments are key. These competitions have an interesting history of formation and development as professional tournaments since 1968. Purpose: to determine the dynamics of the structure and content of key tennis tournaments in the " Open era tennis " and the factors that influenced their formation in different time periods. Material. The article is based on actual data from information resources and publications. Research methods: analysis and synthesis, historical method, systematic approach, comparison. The results. The structure and content of the Wimbledon, US Open, French Open, and Australian Open tournaments have undergone changes throughout the history of their development, and today they have more common features (participants, format of events, number of points to the ranking of athletes, etc.) than differences (coverage of courts, prize fund). Each historical stage of the development of these tournaments is characterized by different influencing factors. The most important are the economic potential of the countries and cities where they are located, local traditions regarding tennis, popularity among the population, etc. The tournaments are held by different organizations, but under the patronage of the ITF, ATP, and WTA, and therefore are part of an agreed competition calendar, which remains stable from year to year. Conclusions. Professional Grand Slam tennis tournaments developed under the influence of factors of the external environment and internal political and economic features of the regions in which they are held. Today it is one of the most anticipated sports spectacles in the whole world, which allows both the organizers of the competitions and their participants to earn high incomes.